Business plan "Garden 48": a guesthouse in Lisbon - Ferreira, Marta Maria Branco dos Santos (2018)
Tourism is one of the most dynamic activity sectors in the world, significantly contributing to a country’s balance of payments. In Portugal, tourism is an engine in the national economy and hospitality has, naturally, developed with it. An evidence of this is the accentuated increase in local accommodation businesses, creating an alternative to hotels (and similar), that pushed the formulation of specific legislative framework in 2014. The present business plan aims to evaluate the pertinence of a local accommodation business in Lisbon, in the category of guesthouse, developed for city breakers and Corporate guests that prioritize discovering the destination (or achieving business purposes for the latter), but still demand quality, convenience and top customer service during the stay. For that reason, the competitive advantage of the guesthouse is to offer key services with maximum quality, eliminating those considered accessory (and dispensable) by the aimed target, providing price benefit. The notion of quality is also highly supported by biophilic design, whose effect on guest well-being is scientifically proven. After literature review on tourism, hospitality (exploring management, guest satisfaction and design notions, amongst others) and biophilic design subjects, the external and internal analysis, the author specifies STP strategic choices and materializes the operational business plan through a 7 Ps marketing mix. The economic and financial analysis revealed a viable business plan, with a 25.220€ NVP, IRR of 4% and a "payback period" of 15 years.